The Intimacy of the Sacred in Kali Worship and Sacrifice - Kuchuk, Nika (Université d'Ottawa | University of Ottawa, 2010)
This paper examines sacrifice in the cult of the goddess Kali, as it is appropriated and practiced both in her native Indian context and within a unique Western setting. I examine the key theme of intimacy and George Bataille's notion of the sacred as both a traumatic and transformative rupture in ordinary reality. Kali's mythos illuminates and animates the practice of blood offering, such as goat sacrifice to Kali in Bengal, as well as the psycho-archetypal, mystic, and mythical aspects of Kali devotion, revealing a persistent continuity between the two forms. Thus, by entering into vastly different sacred landscapes, the experiential aspects of sacrifice interplay between violence and healing, creating an immanent relationship with the sacred other.